Constant Attention and its Correlation with Case Anxiety for Students of the Faculty of Physical Education and Sports Sciences - Jameel Hamid Kadhim (Journal of Global Pharma Technology, 2016)
Students' responses to rapid and changing situations need to be swift, predictable, well-behaved, and control over different attitudes in the course of a lesson, based mainly on higher mental processes (such as attention, perception, perception, thinking and sense). The objective of the search is to learn about the correlation between the constant attention and the anxiety of the case for the students of the Faculty of Physical Education and Sports Sciences for the academic year 2017-2018. The researchers use the descriptive method in the relational relationships to fit and the nature of the search procedures. the research community is the fourth-stage students at the Faculty of Physical Education and Sports Sciences/University of Babylon, of which there are 120 students, while the research sample was the fourth phase students of the (60) divisions (C,D), who were randomly selected from the research community. Through the collection of data and the results obtained, researchers have reached the following conclusions:Students owning a moderate level of attention and anxiety caseHaving a significant correlation between the anxiety of the case and the attention of the research sample.Keywords: Constant attention, Case anxiety and Sports Sciences.